The English Typical Vocabulary Used in Human Resources Departmen of the Oberoi Beach Resort Bali - Pradana, Putu Yogi Sugi; Paramarta, I Made Suta; Suarcaya, Putu (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study employs a qualitative research design, utilizing content analysis and interviews as data collection methods. Content analysis sheets and interview guidelines served as the primary instruments. The research investigates the typical vocabulary used within the Human Resources Department of The Oberoi Beach Resort Bali. The analyzed documents include Training Reports, Standard Operating Procedures (SOPs), Human Resources Reports, Memorandums, Proposals, and the Reward and Recognition Programme documents at The Oberoi Group. Analysis of these documents and interview data revealed 78 typical vocabulary items, aligning with the theoretical framework proposed by Holmes (2013). This analysis highlights the department's focus on maintaining high service standards, adhering to legal frameworks, and ensuring efficient administrative processes. The study concludes that the specific vocabulary used reflects the unique demands of the luxury hospitality industry and underscores the importance of clear and precise communication within the HRD context, as supported by Holmes' (2013) theory.